Longer ground contact time is related to a superior running economy in highly trained distance runners - Tanji, F.; Ohnuma, H.; Ando, R.; Yamanaka, R.; Ikeda, T.; Suzuki, Y. (The Journal of Strength and Conditioning Research, 2024)
Running economy is a key component of distance running performance and is associated with gait parameters. However, there is no consensus of the link between the running economy (RE), ground contact time, and footstrike patterns. Thus, this study aimed to clarify the relationship between RE, ground contact time, and thigh muscle cross-sectional area (CSA) in highly trained distance runners and to compare these parameters between 2 habitual footstrike patterns (midfoot vs. rearfoot). Seventeen male distance runners ran on a treadmill to measure RE and gait parameters. We collected the CSAs of the right thigh muscle using a magnetic resonance imaging scanner. The RE had a significant negative relationship with distance running performance (r = -0.50) and ground contact time (r = -0.51). The ground contact time had a significant negative relationship with the normalized CSAs of the vastus lateralis muscle (r = -0.60) and hamstrings (r = -0.54). No significant differences were found in RE, ground contact time, or normalized CSAs of muscles between midfoot (n = 10) and rearfoot (n = 7) strikers. These results suggest that large CSAs of knee extensor muscles results in short ground contact time and worse RE. The effects of the footstrike pattern on the RE appear insignificant, and the preferred footstrike pattern can be recommended for running in highly trained runners.